MEMBENAHI PENDIDIKAN ISLAM: SUDUT PANDANG, TRADISI DAN PENGALAMAN - Dedi Sahputra Napitupulu; Hasan Bakti Nasution (Reflektika, 2022)
This study aims to highlight the concept of how steps should be taken to improve Islamic education. Using the literature study method, this research shows that the problems of Islamic education that occur today are in aspects of governance or management, the learning process, and the quality of graduates. Meanwhile, the efforts that must be made to solve these problems are equalizing points of view through deliberation, accommodating local wisdom as part of learning activities, and reorientation Islamic education based on experience and productivity.